Party government in Europe? Parliamentary and semi-presidential democracies compared - Schleiter, P; Jones, E (Wiley Blackwell, 2009)
Control over government portfolios is the key to power over policy and patronage, and it is commonly understood to lie with parties in European democracies. However, since the democratic transitions of the 1990s, Europe has had nearly equal numbers of parliamentary and semi-presidential regimes, and there is evidence that the ability of parties to control government posts in these two regime types differs.As yet, political scientists have a limited understanding of the scale and causes of these differences. In this article a principalagent theoretical explanation is proposed. Data are examined on 28 parliamentary and semi-presidential democracies in Europe that shows that differences in party control over government portfolios cannot be understood without reference to the underlying principalagent relationships between voters, elected politicians and governments that characterise Europe’s semi-presidential and parliamentary regimes.